2020
DOI: 10.1371/journal.pone.0241440
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of signal-transducing adaptor protein-1 attenuates experimental autoimmune hepatitis via down-regulating activation and homeostasis of invariant natural killer T cells

Abstract: Objective Signal-transducing adaptor protein (STAP) family members function as adaptor molecules and are involved in several events during immune responses. Notably however, the biological functions of STAP-1 in other cells are not known. We aimed to investigate the functions of STAP-1 in invariant natural killer T (iNKT) cells and iNKT cell-dependent hepatitis. Methods We employed concanavalin A (Con A)-induced hepatitis and α-galactosylceramide (α-GalCer)-induced hepatitis mouse models, both are models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…STAP-1 mutations have been identified in DNA samples from patients with autosomal dominant hypercholesterolemia [21,22], although the effects of STAP-1 in cholesterol homeostasis remain controversial [23,24]. STAP-1 is also involved in autoimmune hepatitis pathogenesis through the regulation of iNKT cell maintenance and/or activation [13]. Microarray data from 572 patients with CML have showed that STAP-1 expression is increased in about 20% samples including ALL with or without BCR-ABL fusion gene [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAP-1 mutations have been identified in DNA samples from patients with autosomal dominant hypercholesterolemia [21,22], although the effects of STAP-1 in cholesterol homeostasis remain controversial [23,24]. STAP-1 is also involved in autoimmune hepatitis pathogenesis through the regulation of iNKT cell maintenance and/or activation [13]. Microarray data from 572 patients with CML have showed that STAP-1 expression is increased in about 20% samples including ALL with or without BCR-ABL fusion gene [25].…”
Section: Discussionmentioning
confidence: 99%
“…Expression vectors for BCR-ABL and STAT5a and their mutant constructs were described previously [8,10]. Myc-tagged STAP-1 was described previously [13]. FLAG-tagged PU.1, RUNX3, NFATc1, and Myc-tagged-STAP-1 deletion mutants were generated by PCR methods and sequenced (primer sequences are available upon request).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Studies have reported that IL2 [371], IGFBP3 [372], IFNG (interferon gamma) [373], GDF15 [374], ACE2 [375] and IGFBP2 [376] could be related to malnutrition. IL2 [377], IGFBP3 [378], FASLG (Fas ligand) [379], BTNL2 [380], ADAMTS1 [381], S100B [382], STAP1 [383], CD160 [384], BANK1 [385], COL4A3 [386], IFNG (interferon gamma) [387], COCH (cochlin) [388], AKT3 [389], CCR4 [390], RAG1 [391], SEMA3A [392], CD200 [393], MYBL1 [394], FCRL3 [395], CD83 [396], GPR174 [397], CD19 [398], IL5 [399], EPHA4 [400], XCL1 [401], IL7R [402], CD180 [403], PRF1 [404], CXCR5 [405], ITM2A [406], ANXA1 [407], CCR6 [408], SLC4A4 [409], GZMB (granzyme B) [410], CD69 [411], BTLA (B and T lymphocyte associated) [412], IGF2 [413], SDC1 [414], MMP9 [415], GDF15 [416], C1QA [417], HRH3 [418], ACE2 [419...…”
Section: Identification Of Degsmentioning
confidence: 99%
“…STAP-1 gene mutations have been shown in some patients with autosomal dominant hypercholesterolemia [24,25]; however, the STAP-1's functional role in cholesterol homeostasis remains questionable [26,27]. STAP-1 acts to control the maintenance and activation of invariant natural killer (NK) T-cells and is involved in the pathogenesis of autoimmune hepatitis [28]. STAP-1 also plays a critical role in the maintenance of chronic myeloid leukemia leukemic stem cells [29].…”
Section: Stap Proteinmentioning
confidence: 99%